Implications of prolonged sub-zero environmental conditioning and temperature cooling on the microstructural morphological, and mechanical properties of SiC reinforced Al6061-T6 friction stir spot welded joints - Neeru Chaudhary; Sarbjit Singh; Mohinder Pal Garg; Hreetabh Kishore; Shubham Sharma; Shashi Prakash Dwivedi; Mohamed Abbas; M. Ijaz Khan; Emad Makki (Journal of Materials Research and Technology, 2024)
Friction stir spot welding (FSSW) is a prominent solid-state adhesion process. In the recent past, several investigations are performed for the property enhancement of FSSW welded joints especially on the mechanical and metallurgical characterization. In this work, an attempt has been made to analyze the effect of environmental conditions on the output quality characteristics of SiC reinforced Al6061-T6 welded joints, fabricated at optimal parametric setting. For this, welded joints are preserved at sub-zero temperature of −18 ± 2 °C for 90, 180, 270 and 360 days. Output quality characteristics in terms of tensile-shear and micro-hardness test in combination with microstructure analyses using SEM, EDS Mapping, and XRD analysis are emphasized. It is revealed that during sub-zero cooling, weld strength and micro-hardness of weldments increased over time. Additionally, a decrease in crystal size and increase in dislocation density are observed with increase in cooling period of weld joint, which eventually made suitable for extreme applications.